Depression, everyday technology use and life satisfaction in older adults with cognitive impairments: a cross‐sectional exploratory study. Issue 1 (22nd March 2020) - Köttl, Hanna; Fallahpour, Mandana; Hedman, Annicka; Nygård, Louise; Kottorp, Anders
Abstract : Rational: Life satisfaction is strongly associated with participation in everyday life activities. Yet, older adults with cognitive impairments have been found to experience difficulties in accessing and engaging in more complex everyday activities, especially, if these involve everyday technology. Considering the rapidly advancing technological landscape, this may substantially affect individuals' life satisfaction and their participation in meaningful community‐based and home‐based activities. Objectives: This study aimed to explore the associations between life satisfaction, ability to use everyday technology and number of relevant everyday technologies used in older adults (n = 117) with and without mild cognitive impairment (MCI) and Alzheimer's disease (AD). It also aimed to understand the role of depression, activity involvement and diagnosis regarding life satisfaction in this sample. Method: Descriptive statistics, Mann–Whitney U tests and t ‐tests were applied to compare those satisfied and those dissatisfied with life regarding ability to use everyday technology and number of relevant everyday technologies used. Findings: The number of relevant community‐based everyday technologies currently not used was significantly associated with being dissatisfied with life (p < 0.05). Further, depression and withdrawal from activities and interests significantly differed across life satisfaction groups, while no group differences were found regarding overall number of everyday technologies in use and ability to use everyday technology. Conclusion: Attention from healthcare professionals and researchers to early withdrawal from activities that rely on community‐based everyday technologies is called for, especially in older adults with depression. Preventing everyday technology‐related barriers in community life may increase life satisfaction.